2000
DOI: 10.1159/000029933
|View full text |Cite
|
Sign up to set email alerts
|

Dithranol in a Cream Preparation: Disperse or Dissolve?

Abstract: In the search for the ideal dithranol cream preparation for short-contact treatment of psoriasis, we investigated the clinical efficacy, side effects and patient appreciation of two dithranol cream preparations (cream A and B) in a double-blind left-right comparing study. Dithranol was dissolved at preparation in cream A and dispersed in cream B. Cream A is known to have a shelf life of 1 year, while cream B has a much shorter shelf life (several months). Ten patients with chronic plaque-type psoriasis were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…A total of 15 studies fulfilled the criteria for inclusion in the guidelines. For dithranol monotherapy, there was one grade A 2 study [96], 11 grade B studies [97–107], and 1 grade C study [108]. The result is an evidence level of 2.…”
Section: Topical Therapymentioning
confidence: 99%
“…A total of 15 studies fulfilled the criteria for inclusion in the guidelines. For dithranol monotherapy, there was one grade A 2 study [96], 11 grade B studies [97–107], and 1 grade C study [108]. The result is an evidence level of 2.…”
Section: Topical Therapymentioning
confidence: 99%
“…For dithranol monotherapy, there was one grade A 2 study [96], 11 grade B studies [97][98][99][100][101][102][103][104][105][106][107], and 1 grade C study [108]. For dithranol monotherapy, there was one grade A 2 study [96], 11 grade B studies [97][98][99][100][101][102][103][104][105][106][107], and 1 grade C study [108].…”
Section: Efficacymentioning
confidence: 99%
“…Various efforts like chemical modifications of the molecule, formulation changes, new treatment modifications or strategies and other miscellaneous approaches like short-contact therapy did not provide any definite solution. [68][69][70] Subsequent work on liposomal systems with dithranol led to the improvement in its skin penetration. [71] Agarwal et al developed dithranol entrapped in liposomal and niosomal vesicles (0.5%) and found both of them superior to conventional formulation, while liposomes showed better results than niosomes employing mice skin.…”
Section: Dithranolmentioning
confidence: 99%
“…[94][95][96][97][98] Only preclinical animal studies with liposomes and nanoparticles of tacrolimus have been reported with improved skin transport effect. [69][70] Theophylline derivatives Dyphylline, a derivative of theophylline, inactivates cyclic AMP (cAMP), and is, therefore, used in the management of psoriasis. [99] Touitou et al (1992) reported significant increase in permeation of dyphylline across abdominal mice skin using liposomal systems, thus corroborating its promise in topical delivery.…”
Section: Dithranolmentioning
confidence: 99%